ДО ПИТАННЯ ПРО РОЗМІЩЕННЯ НАКОПИЧУВАЧІВ ЕНЕРГІЇ В ОЕС УКРАЇНИ - Буткевич , О.Ф.; Юнєєва , Н.Т.; Гурєєва , Т.М. (Інститут електродинаміки НАН України, Київ, 2019)
To balance stochastic changes in the power of renewable energy sources in the interconnected power system (IPS) of Ukraine it is planned to use energy storages (ES). It is shown that during ES placing it is necessary to take into account their influence on power flows of controlled cutsets of the IPS of Ukraine. References 1, tables 3, figures1.